Sex allocation in inflorescences of the self-compatible Polygonatum verticillatum (Liliaceae) - Guitián, Javier; Guitián, Pablo (Mediterranean Botany, 2022)
The modularity and sequential flower production in hermaphroditic plants enable them to modify sex allocation in response to biotic or abiotic environmental variation. To test three predictions derived from the relationship between sexual specialization and compatibility levels, we analyzed the breeding system (self-incompatibility) of Polygonatum verticillatum and the variation in sexual investment to stamens, ovules, pollen grains and P:O ratio among flowers at different positions of the inflorescence. Our results show that in self-compatible P. verticillatum sexual investment varies throughout the inflorescence with an increase in the number of pollen grains but does not show male specialization in top flowers, unlike other self-incompatible species of the genus previously studied. Comparative studies of the variation in floral sex allocation between taxonomically close species should contribute to a better interpretation of the relationships between sexual investment and the breeding system.